Beliefs towards mental illness in Turkish physiotherapy students - DEMİRBÜKEN, İLKŞAN; YURDALAN, SAADET UFUK (TAYLOR & FRANCIS INC, 2015)
Mental health is a new area of specialization for physiotherapists. However, they usually meet patients with psychiatric co-morbidities secondary to other chronic diseases. It is important to explore the beliefs of future physiotherapists regarding mental illness in order to implement effective strategies to avoid possible stigmatizing attitudes that may interfere with the rehabilitation process. Moreover, the psychiatric field should be introduced to physiotherapists as a clinical and research area. Therefore, we aimed to question the beliefs of physiotherapy students regarding mental illness using the Beliefs towards Mental Illness Scale in two different universities in Turkey. The total score of 524 students was 46.5 +/- 14.5 out of 105 while the Dangerousness Subscale score was 21.2 +/- 5.8/40; Incurability and Poor Social and Interpersonal Skills Subscale score was 24.2 +/- 9.3/55 and Shame Subscale score was 1.1 +/- 1.9/10. Students who had a relationship with an individual having a mental problem and students who had consulted a psychiatrist/psychologist for any mental problem showed more positive beliefs. Future physiotherapists should be informed and trained regarding people with mental illness both to avoid stigma and to be aware of this area in physiotherapy settings. Therefore, it is important to implement new curricula for schools providing physiotherapy education including courses, lectures and clinical practices in the psychiatry field.
Keywords: Beliefs; mental illness; physiotherapy students; HEALTH PROFESSIONALS; ATTITUDES; STIGMA; RELIABILITY; VALIDITY; SCALE